2019
DOI: 10.1038/s41598-018-37835-6
|View full text |Cite|
|
Sign up to set email alerts
|

Differentiating between cancer and normal tissue samples using multi-hit combinations of genetic mutations

Abstract: Cancer is known to result from a combination of a small number of genetic defects. However, the specific combinations of mutations responsible for the vast majority of cancers have not been identified. Current computational approaches focus on identifying driver genes and mutations. Although individually these mutations can increase the risk of cancer they do not result in cancer without additional mutations. We present a fundamentally different approach for identifying the cause of individual instances of can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 67 publications
2
34
0
Order By: Relevance
“…Dash et al [97] proposed a method for identifying two-hit combinations that are likely responsible for carcinogenesis. The authors represented the problem as an instance of the weighted set cover problem [98] and showed that the identified set of combinations could discriminate normal and cancer samples with high accuracy.…”
Section: Comparison Of Crso With Weighted Set Covering Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Dash et al [97] proposed a method for identifying two-hit combinations that are likely responsible for carcinogenesis. The authors represented the problem as an instance of the weighted set cover problem [98] and showed that the identified set of combinations could discriminate normal and cancer samples with high accuracy.…”
Section: Comparison Of Crso With Weighted Set Covering Approachesmentioning
confidence: 99%
“…However, there is a major difference in the optimization criteria in each of the methods. In [97] sets of combinations are prioritized based on how well they can discriminate normal and tumor samples in a training set. This choice of criteria assumes that combinations that occur only in tumors are likely to be cooperating drivers.…”
Section: Comparison Of Crso With Weighted Set Covering Approachesmentioning
confidence: 99%
“…Dash et al [28] recently proposed an innovative method for identifying two-hit combinations that are likely responsible for carcinogenesis. The authors represented the problem as an instance of the weighted set cover problem [29] and showed that the identified set of combinations could discriminate normal and cancer samples with high accuracy.…”
Section: # Eventsmentioning
confidence: 99%
“…However, there is a major difference in the optimization criteria in each of the methods. In [28] sets of combinations are prioritized based on how well they can discriminate normal and tumor samples in a training set. This choice of criteria assumes that combinations that occur only in tumors are likely to be cooperating drivers.…”
Section: # Eventsmentioning
confidence: 99%
See 1 more Smart Citation